Development and validation of a Delphi consensus-based questionnaire for the multidisciplinary management of type 2 inflammation-related diseases - Ortiz de Frutos, Francisco Javier; Cisneros, Carolina; Villacampa, José Miguel; Palomares, Óscar; Dávila, Ignacio (Frontiers in Allergy, 2025)
ObjectiveThis study aimed to validate a 15-item screening questionnaire for the early detection of coexisting type 2 (T2) inflammatory diseases, such as asthma, atopic dermatitis, and chronic rhinosinusitis with nasal polyps (CRSwNP), among others.MethodsThe questionnaire, designed through expert consensus by a scientific committee, underwent Delphi methodology for validation. A multidisciplinary panel of 19 clinicians from different specialties reviewed the questionnaire for clinical relevance, while 39 patients from different regions of Spain evaluated its comprehensibility.ResultsThe clinician panel reached a consensus on the relevance of 13 out of 15 items in the first round and agreed that a single positive response was sufficient to justify referral to the appropriate specialist. Two items were modified and validated in the second round. The patient panel unanimously agreed on the comprehensibility of the questionnaire in the first round. Linguistic variations were also ranked to ensure clarity across regions, further enhancing the validation of the tool.ConclusionThis validated questionnaire offers a practical tool for early detection of T2 inflammatory diseases. Its simplicity and comprehensibility, confirmed by clinicians and patients, make it suitable for use in various healthcare settings, supporting timely specialist referrals and improved patient care. Future studies will evaluate its effectiveness in real-world clinical practice.